FRASA PREPOSISIONAL DALAM KUMPULAN CERPEN 'SENJA DAN CINTA YANG BERDARAH' KARYA SENO GUMIRA AJIDARMA - Anisah Hanif (Mahakarya: Jurnal Mahasiswa Ilmu Budaya, 2020)
This study aimed to determine the functional structure of sentences containing prepositional phrases and categorical patterns of prepositional phrase fillers in the short story Senja dan Cinta yang Berdarah written by Seno Gumira Adjidarma. The focus of this research is the prepositional phrase markers. This research is a descriptive qualitative research. Data collection was carried out by the listening method followed by the advanced note-taking technique. The data analysis technique used is the distribution technique with the basic technique for Direct Elements (BUL). The results of this study indicate that the functional structure of sentences found 25 patterns. Based on the categorical pattern of prepositional phrase fillers in, to, and from the found 11 patterns. The use of prepositional phrases in the short stories serves to state the setting or place of existence and the media. The prepositional phrase to serves to express the setting or destination. Then the prepositional phrase of the function is to state the setting or place of origin.